PENGARUH MORAL WAJIB PAJAK, SISTEM PERPAJAKAN, DAN RESIKO AUDIT PADA WAJIB PAJAK BADAN TERHADAP KEPATUHAN WAJIB PAJAK - , INDRA ADITYAS P; , Eko Suwardi, Dr., M.Sc., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper examines the effect of tax moral, tax system quality, and audit risk for corporate taxpayers towards tax compliance. The purpose of this paper is to seek empirical proof does those factors affecting tax compliance have a positive effect and play a significant role for corporate tax compliance in Indonesia. The researcher decides to sample corporate taxpayers for bussinesman in Daerah Istimewa Yogyakarta. A survey questionnaire is distributed to the sample during November 2013 by workshop or seminars and personal as research data. The results of this paper showed that all variables: tax moral, tax system quality, and audit risk shows a positive effect towards tax compliance. The findings of this research implied that the government should put more concern in terms or service quality, transparency, and tax related facts to be informed for new corporate taxpayers. Government for Directorate General of Taxation should also have a good tax morale, in order to be an example of a taxpayer who is already old and new, in order to create a sense of trust from corporate taxpayers.